Jody Butterfield, Sam Bingham, Allan Savory. Holistic Management: Handbook: Regenerating your land and growing your profits, 3rd ed. 2019, Island Press, 2000 M Street, NW, Suite 650, Washington, DC 20036. 250 p. Hardcover and Ebook. - Flores, Paulina G. (Agro Sur, 2020)
In “Holistic Management Handbook”, Jody Butterfield, Sam Bingham and Allan Savory offer a fascinating step-by-step method for running a farm using a holistic management approach with tangible results. In this third edition, the authors bring their vision to the responsibility to restore our environment, and describe how to do it. This vision has clear instructions that focus on: plan-monitor-control-replan. The handbook has been thoroughly revised and explains the planning procedures described in the book “Holistic Management: a Commonsense Revolution to Restore Our Environment” (Savory and Butterfield, 2016). The major revisions enlarged are the holistic perspective to manage natural systems, natural processes and cycles (water, mineral, community dynamics, and energy), and nature’s function in relationship with people, animals, and land (time management, stock density, cropping, burning). Both books are complementary in theory and practice, as together they explain how land is restored by livestock and the gains made from the land through holistic management. The chapters 2 and 3 conclude with examples of worksheets for grazing plans, monitoring procedures, and chapter 4 offers Appendices about ecological monitoring forms. The handbook includes a comprehensive glossary of terms...